Socio-economic Drivers of Smart Waste Management Implementation in the South African Construction Industry - Iyiola, Comfort Olubukola; Shakantu, Winston (Journal of Construction in Developing Countries, 2026)
In many developed countries, smart waste management (SWM) is widely used to minimise material waste, improve resource efficiency and support environmental sustainability. However, the construction sector in developing regions continues to exhibit poor waste management practices, resulting in negative impacts on the built environment. Therefore, this study explores the socio-economic drivers of SWM implementation in South Africa’s construction sector. To gather relevant insights into these drivers, structured questionnaires were distributed to construction professionals using purposive and snowball sampling. The results show that all 25 socio-economic drivers were statistically significant in the implementation of SWM in the construction industry. The Shapiro-Wilk test was used to assess whether the dataset followed a normal distribution and the results indicated that a non-parametric analysis was required. Consequently, the Kruskal-Wallis H-test was applied, which showed significant differences in the respondents’ views regarding the identified drivers. Factor analysis categorised the socio-economic drivers into six categories: financial and resource efficiency, environmental sustainability, policy and regulatory, organisational and managerial, social and human capital, and stakeholder collaboration. The study concludes that the highlighted socio-economic drivers play a critical role in supporting the adoption of SWM within the South African construction industry.